Analisa Peran Tenaga Honorer Terhadap Efektivitas Tugas Aparatur Sipil Negara - Rezkia Dora (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2020)
One of the factors of the implementation of the task of the State Civil Apparatus is the role of honorary personnel in each Government agency. In the Rangsang Barat District Office, part of the State Civil Apparatus task was handed over to honorary personnel. However, there is a lack of clarity in the assignment of each honorary staff, causing the role of honorary personnel to be ineffective. The issue of the role of honorary workers has been raised by the authors in the research. The purpose of this research is to analyze other factors that cause ineffectiveness of the role of honorary personnel and provide solutions to problems. This study used descriptive qualitative method. In analyzing the role of honorary personnel in the Rangsang Barat District Office, researchers looked at three factors, namely the main tasks of the State Civil Apparatus, the criteria and procedures for the appointment of honorary personnel, and the implementation of the duties of honorary personnel at the Rangsang Barat District Office. Based on these three factors it can be concluded that the role of honorary workers in the Rangsang Barat District Office is less effective.